Detection of LiveLock in BPMN using process expression - Tantitharanukul N. (2017)
Although the Business Process Modeling Notation (BPMN) is a popular tool for modeling business process in conceptual level, the result diagram may contain structural problem. One of the structural problems is livelock. In this problem, one token proceeds to end event, while other token is still in process with no progression. In this paper, we introduce an expression liked method to detect livelock in the BPMN diagram. Our approach utilizes the power of the declarative ability of expression to determine all of the possible process chains, and indicate whether there are livelock or not. As a result, we have shown that our method can detect livelock, if any. © 2010 Springer-Verlag.